A Chromatin-Focused siRNA Screen for Regulators of p53-Dependent Transcription. Issue 8 (1st August 2016) - Sammons, Morgan A; Zhu, Jiajun; Berger, Shelley L
Abstract: The protein product of the Homo sapiens TP53 gene is a transcription factor (p53) that regulates the expression of genes critical for the response to DNA damage and tumor suppression, including genes involved in cell cycle arrest, apoptosis, DNA repair, metabolism, and a number of other tumorigenesis-related pathways. Differential transcriptional regulation of these genes is believed to alter the balance between two p53-dependent cell fates: cell cycle arrest or apoptosis. A number of previously identified p53 cofactors covalently modify and alter the function of both the p53 protein and histone proteins. Both gain- and loss-of-function mutations in chromatin modifiers have been strongly implicated in cancer development; thus, we sought to identify novel chromatin regulatory proteins that affect p53-dependent transcription and the balance between the expression of pro-cell cycle arrest and proapoptotic genes. We utilized an siRNA library designed against predicted chromatin regulatory proteins, and identified known and novel chromatin-related factors that affect both global p53-dependent transcription and gene-specific regulators of p53 transcriptional activation. The results from this screen will serve as a comprehensive resource for those interested in further characterizing chromatin and epigenetic factors that regulate p53 transcription.